Teachers’ Use of Humor in English as a Foreign Language (EFL) Classrooms - Rizky, Debby; Husein, Rahmad; Hutasuhut, Mahmud Layan (Jurnal Bahasa dan Sastra, 2024)
A pleasant environment is essential for student motivation and interaction, and effective classroom management plays a key role in this. Utilizing humor in teaching creates a more welcoming and humanistic classroom atmosphere, thereby improving the overall teaching-learning process. This study aims to identify the categories of humor employed by English teachers in the classroom. A qualitative descriptive method was used for the research. Six English class sessions were observed and recorded. The data for this study consisted of humor-containing utterances made by English teachers. The analysis classified teacher humor into two main categories: appropriate and inappropriate forms. Most of the humor used by teachers fell into the appropriate category, with the majority being related to the class material, followed by humor unrelated to the subject being taught. A small portion of inappropriate humor included self-deprecating humor, while another small portion was unintentional or unplanned. In contrast, inappropriate humor was rare and typically involved derogatory comments directed at others. These findings highlight that most of the humor used was lesson-related and aligned with pedagogical objectives, while inappropriate humor was infrequent. The results suggest that humor in the classroom is primarily used as a positive pedagogical tool, contributing to an engaging and supportive learning environment. Future research should explore the impact of different humor categories on student learning outcomes and classroom dynamics.